2021
DOI: 10.1007/s12369-021-00812-7
|View full text |Cite
|
Sign up to set email alerts
|

From HRI to CRI: Crowd Robot Interaction—Understanding the Effect of Robots on Crowd Motion

Abstract: How does the presence of a robot affect pedestrians and crowd dynamics, and does this influence vary across robot type? In this paper, we took the first step towards answering this question by performing a crowd-robot gate-crossing experiment. The study involved 28 participants and two distinct robot representatives: A smart wheelchair and a Pepper humanoid robot. Collected data includes: video recordings; robot and participant trajectories; and participants’ responses to post-interaction questionnaires. Quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
1
3
1
Order By: Relevance
“…This is in line with a part of the current literature, such as works by Xie et al [43] and Vassallo et al [44], who noticed no difference in HRI and non-HRI activities. Most of the literature argued that an influence is created by the presence of the robot in a working environment [40][41][42]. The difference between the results of the present study and the other contrasting studies can be explained by the monitored parameters in the papers.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This is in line with a part of the current literature, such as works by Xie et al [43] and Vassallo et al [44], who noticed no difference in HRI and non-HRI activities. Most of the literature argued that an influence is created by the presence of the robot in a working environment [40][41][42]. The difference between the results of the present study and the other contrasting studies can be explained by the monitored parameters in the papers.…”
Section: Discussioncontrasting
confidence: 82%
“…Huber et al [40] demonstrated that robots influence the behavior of humans in simple tasks as well, such as the ones implying hand movements. Similar results were found by Zhang et al [41], whose empirical study demonstrated that robots affect humans in some actions, influencing the completion times and trajectories followed. The same results are confirmed by Chen et al [42], who observed that people changed behavior according to their anticipation of a potential collision with robots during pedestrian motion.…”
Section: Literature Reviewsupporting
confidence: 89%
“…It can be seen from the above that the random forest algorithm has many improvement ways and a wide range of application fields, and it has its unique advantages compared with other algorithms in data classification and prediction. Therefore, random forest is a relatively mature and excellent machine learning algorithm in machine learning [ 6 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…-see the standardized circuits in [1]. Follow-up studies are necessary to address these situations, including avoiding dynamic obstacles like pedestrians walking [41].…”
Section: Discussionmentioning
confidence: 99%